FAKTOR-FAKTOR YANG MEMENGARUHI FIRM VALUE PADA PERUSAHAAN NON KEUANGAN DI INDONESIA - Virya Dhyani; Widyawati Lekok (E-Jurnal Akuntansi TSM, 2022)
This study aims to gather empirical proof about wether tax avoidance, Return on Asset, Current Ratio, Leverage, firm size, Dividend Payout Ratio and investment decision affect firm value. The population of this study is non finance companies that are listed in Indonesia Stock Exchange on 2018-2020. Selection of samples in this research was based on purposive sampling technique with total 291 data sample used. This study used multiple regression model. This study finds that Return on Asset, Leverage and firm size have significant effect to firm value. On the other side, tax avoidance, current ratio, dividend payout ratio and investment decision do not affect firm value.